Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1101/2022.12.23.521791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exogenous attention interferes with endogenous attention processing via lateralized alpha power

Abstract: Current theories of attention differentiate exogenous (bottom-up) from endogenous (top- down) orienting of visuospatial attention. While both forms of attentional processing engage different processes, endogenous and exogenous attention are thought to share processing resources, as shown by recent empirical evidence of their functional interactions. Here, we aim to uncover the neurobiological basis of how salient events that drive exogenous attention disrupts endogenous attention processes. We hypothesize that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(46 reference statements)
2
1
0
Order By: Relevance
“…These results denote that beyond early differential effects, exogenous and endogenous impact sensory processing in a similar fashion. These results support growing literature suggesting that these attention processes share neural processes at the sensory level (Landry et al, 2022). Likewise, our mediation analysis also shows analogous effects for the second and third component (which corresponded to a contralateral component and a more centroparietal topographical pattern, respectively; see Appendix B).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These results denote that beyond early differential effects, exogenous and endogenous impact sensory processing in a similar fashion. These results support growing literature suggesting that these attention processes share neural processes at the sensory level (Landry et al, 2022). Likewise, our mediation analysis also shows analogous effects for the second and third component (which corresponded to a contralateral component and a more centroparietal topographical pattern, respectively; see Appendix B).…”
Section: Discussionsupporting
confidence: 90%
“…This outcome is consistent with results from brain imaging (e.g., Dugué, Merriam, Heeger, & Carrasco, 2020). Our recent EEG work aligns with these findings and showed that exogenous and endogenous attention interfere with each other early during visual processing (Landry, da Silva Castanheira, Raz, Baillet, & Sackur, 2022).…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation